Everybody wants ‘good teachers’ – but they are hard to define A common narrative of model educators: from fictional teachers through exceptional educators to current educators’ professional perceptions - Bar Gosen, Noah (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Throughout the years. researchers searched for the definition of a good teacher. This article offers to learn from model educators, fictional and historical, how to define values, perception and practices which characterize good teachers. Four fictional teachers were chosen based on two characteristics: First, author’s descriptions that underline their good qualities as a person and as a teacher. Second, remarks from their students’ and/or students’ parents or guardians, stating their acknowledgment of the teachers’ special qualities. and their gratitude for the learning experience they shared. A qualitative narrative analysis of these teachers – ‘Jane Eyre’, ‘Ann of Green Gables’ and his sequel ‘Anne from Avonlea”, ‘Up the down Staircase’ and ‘Goodbye Mr. Chips’ – defined five major characteristics which represent the exceptional teacher: holistic perception of the student, identifying and addressing students’ unique needs, emphasis on student-teacher relationship, creative teaching, a sense of mission and an inspiring personality. Examining the work of exceptional educators such as Ann Sullivan (Helen Keler’s tutor). Janusz Korczak, and Haime Escelante, reveals common themes which corresponds with fictional model teachers characteristics. Qualitative interviews with 14 Israeli rural high school teachers (7 homeroom educators and 7 subject teachers) emphasized similar characteristics of their role perceptions and practices. The key to higher achievements, educational and academic alike, lies in the hands of the teachers. If these traits characterize the ‘good teacher’ we should consider merging then into teachers’ preparatory and in-work professional training, as well as teachers’ evaluation processes. Let us learn from good examples how to become ‘good teachers’.